Extracellular enzymes of Colletotrichum fructicola isolates associated to Apple bitter rot and Glomerella leaf spot - Aline Cristina Velho (Mycology, 2018)
Colletotrichum fructicola causes two important diseases on apple in Southern Brazil, bitter rot (ABR) and Glomerella leaf spot (GLS). In this pathosystem, the Colletotrichum ability to cause different symptoms could be related to differences of extracellular enzymes produced by the fungi. Thus, the objectives of this study were to compare the production of these enzymes between ABR- and GLS-isolate in vitro and to evaluate their involvement on infected apple leaves with C. fructicola. In agar plate enzymatic assay, ABR- showed significantly higher amylolytic and pectolytic activity than GLS-isolate. In contrast, for lipolytic and proteolytic no significant differences were observed between isolates. In culture broth, ABR-isolate also had higher activity of pectin lyase (PNL), polygalacturonase (PG) and laccase (LAC). Notably, LAC was significantly five-fold higher in ABR- than GLS-isolate. On the other hand, in infected apple leaves no significant difference was observed between isolates for PNL, PG and LAC. Although differences in extracellular enzymes of ABR- and GLS-isolate have not been observed in vivo, these results contributed to highlight the importance to investigate such enzymes in depth.